Theoretical study of “trapping sites” in cryogenic rare gas solids doped with β-dicarbonyl molecules - Rojas-Lorenzo, G.; Lara-Moreno, M.; Gutiérrez-Quintanilla, A.; Chevalier, M.; Crépin, C. (Физика низких температур, 2019)
A deposition model to simulate the growth of doped rare gas crystals is used. The study involves organic
molecules with a single intramolecular hydrogen bond such as malonaldehyde, 2chloromalonaldehyde and
acetylacetone as impurities. Different trapping sites were obtained depending on the rare gas properties for a given impurity, and depending on the molecular size and shape for a given crystal. Simulations were carried out by
using classical molecular dynamics methods including an anharmonic thermal correction, to take into account
the zero point movement of the crystal. The results are correlated to spectroscopic data previously achieved for
these systems by steady state IR spectroscopy. Для імітації росту допованих кристалів інертного газу використана модель осадження. В якості домішок розглянуто
органічні молекули з одним внутрішньомолекулярним водневим зв'язком: малональдегід, 2-хлормалональдегід та ацетилацетон. Залежно від властивостей кристала інертного газу, а
також розмірів й форм молекул домішок отримано характеристики різних «пасток». Моделювання проводилося з використанням методів класичної молекулярної динаміки, включаючи ангармонічне наближення, з урахуванням нульових
коливань кристала. Результати корелюють з отриманими
раніше для цих систем даними ІЧ-спектроскопії. Для имитации роста допированных кристаллов инертного
газа использована модель осаждения. В качестве примесей рассмотрены органические молекулы с одной внутримолекулярной водородной связью: малональдегид, 2-хлормалональдегид
и ацетилацетон. В зависимости от свойств кристалла инертного газа, а также размеров и форм молекул примесей получены характеристики различных «ловушек». Моделирование
проводилось с использованием методов классической молекулярной динамики, включая ангармоническое приближение, с учетом нулевых колебаний кристалла. Результаты коррелируют с полученными ранее для этих систем данными
ИК-спектроскопии.